Network society and future scenarios for a collaborative economy - Kostakis, Vasilis; Bauwens, Michel (Basingstoke, 2014)
"The aim of this book is not to provide yet another critique of capitalism but rather to contribute to the ongoing dialogue for post-capitalist construction, and to discuss how another world could be possible. It builds on the idea that peer-to-peer infrastructures are gradually becoming the general conditions of work, economy, and society, considering peer production as a social advancement within capitalism but with various post-capitalistic aspects in need of protection, enforcement, stimulation and connection with progressive social movements. Using a four-scenario approach, the authors seek to simplify possible outcomes and to explore relevant trajectories of the current techno-economic paradigm within and beyond capitalism. They postulate that the mature peer production communities pose a sustainable alternative to capital accumulation, that of the circulation of the Commons. They make some tentative transition proposals towards a Commons-based economy and society for the state, the market and the civic domain."